Effects of Extract of Male Papaya Leaves (Carica papaya L.) on Macrophage Polarization (M1/M2) in Chronic Inflammation and Cancer Models - Lisa Savitri; Kharisul Ihsan; Elfred Rinaldo Kasimo (Biology, Medicine, & Natural Product Chemistry, 2026)
Chronic inflammation plays a central role in the pathogenesis of various diseases, including cancer, and is closely associated with dysregulated macrophage polarization. Macrophages exhibit high plasticity and can differentiate into pro-inflammatory (M1) or anti-inflammatory/tumor-promoting (M2) phenotypes. Targeting macrophage polarization has emerged as a promising therapeutic strategy to restore immune balance and inhibit tumor progression. This study aimed to investigate the effects of male papaya (C. papaya L.) leaf extract on macrophage polarization (M1/M2) in models of chronic inflammation and cancer. An experimental approach was employed using both in vitro and in vivo models. Male papaya leaves were extracted using 70% ethanol and subjected to phytochemical analysis. In vitro studies were conducted using RAW 264.7 macrophages induced into M1 (LPS/IFN-gamma) and M2 (IL-4) phenotypes, followed by treatment with varying concentrations of the extract. Macrophage polarization was assessed through gene and protein expression of specific markers (iNOS, TNF-alpha, IL-6, Arg-1, CD206, IL-10), nitric oxide (NO) production, and analysis of signaling pathways (NF-kB, STAT1/STAT6, PI3K/Akt). A macrophage–cancer cell co-culture system was used to evaluate effects on cancer cell proliferation, migration, and apoptosis. In vivo studies were performed using mouse models of chronic inflammation and tumor induction. The results demonstrated that male papaya leaf extract contains significant levels of phenolic and flavonoid compounds and exerts a dose-dependent immunomodulatory effect. The extract reduced M1-associated pro-inflammatory markers and nitric oxide production while also suppressing excessive M2 polarization markers, indicating a rebalancing effect on macrophage phenotypes. Mechanistically, these effects were associated with the inhibition of NF-kB and modulation of STAT1/STAT6 and PI3K/Akt signaling pathways. In cancer models, extract-treated macrophages reduced tumor cell proliferation and migration while increasing apoptosis. In vivo findings further confirmed reduced tumor growth and a shift toward anti-tumor macrophage activity. In conclusion, male papaya leaf extract exhibits significant potential as a natural immunomodulatory agent by regulating macrophage polarization in chronic inflammation and cancer. These findings provide a scientific basis for the development of plant-based therapeutic strategies targeting immune regulation. Further studies are needed to isolate active compounds and evaluate clinical applications.